Simulation Study of the Roof Fracture Pattern of a Horizontal Sublevel Caving in a Steeply Inclined Thick Coal Seam. (5th August 2020) - Kang, Xin; Yang, Sheng-li; Zhan, Ping; Li, Liang-hui
Abstract : Application of a horizontal section top-coal caving in a steeply inclined thick coal seam not only effectively resolves the problem of the large dip angle of the coal seam and slipping and dumping of mining equipment but also significantly reduces the tunnel drivage ratio and improves the extraction yield. In addition, it allows for a safe and efficient mining from a steeply inclined thick coal seam. In this paper, the roof fracture pattern of a steeply inclined thick coal seam has been studied by a similar simulation experiment. The results of the simulation are consistent with those of the numerical calculations, thus verifying the accuracy of the simulation. The experimental simulation results show that the roof can form a step-like toppling failure pattern after drawing the coal, and it is difficult to release a triangular coal mass near the floor, which is the main concentration area of coal loss. The numerical simulation results show that, with the excavation of the coal seam, the rock mass around the goaf produces plastic failure, and the damage is mainly concentrated in the roof area. The upper part of the goaf mainly shows a tensile failure, while the other areas mainly show yield failure.